An overview and an account (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
There are three teachings that Solomon’s book gives us:The city is not a summation of serial parts, aggregated as modules of a submarine, but an organism of parts linked by instances of necessity. Contrary to the heroic image conveyed by the stars of contemporary architecture that sees users as spectators, the architect is a silent and anonymous civil servant who puts his profession at the service of the community. Large cultural movements such as New Urbanism that have changed people’s feelings about housing and city issues require strict continuous self-criticism to maintain an avant-garde role in exercising discipline and not falling into the fashion routine.Â